Stress analysis in propeller cage design / Mohd Noorkhairi Mahmud and Nurfadli Mohd Salim - Mahmud, Mohd Noorkhairi; Salim, Nurfadli Mohd (2004)
The problem arises from the company of North Port (M) Bhd. Klang having high maintenance on repairing the propeller blade. It is found that the damaged is cause by hitting object to the blade during operation. Its is more expensive to repair and to order the propeller cage from supplier. Therefore it is more economical to make own design of the propeller cage to solve the problem by covering the propeller by using a guard.